Relative size matters: Spawning substrate roughness size and spacing affect egg dislodgement and retention in the benthos - Jake Carman; Yingming Zhao; Josef D. Ackerman (Limnology and Oceanography, 2024)
The consequences of hydrodynamic effects on survival of embryonic benthic organisms remain unknown. This is because the interaction of hydrodynamics and substrate roughness is complex, but it can be conceptualized in two dimensions by roughness flow regimes (isolated, wake interference, and skimming flow) or roughness types ( k ‐ and d ‐type). We examined the effect of different roughness flow regimes/roughness types and roughness heights ( k ) on the dislodgement of walleye ( Sander vitreus ) eggs (2 mm diameter, ⌀) using a wall jet apparatus. We expected that lower wall shear stress ( τ w ) would be required for dislodgement in more‐exposed/less‐sheltered roughness type/flow regimes (i.e., k ‐type/isolated roughness flow) and when k ≤ ⌀. Surprisingly, the opposite was found, indicating that other mechanism(s) are also responsible for egg dislodgement on these rough surfaces. Hydrodynamic sheltering occurred when flow was directed over exposed eggs ( k ≤ ⌀) adjacent to roughness elements effectively increasing their width, and thus requiring higher τ w for rolling and then ejection. When k > ⌀, eggs dislodgement likely occurred via the lower pressure in the eddies recirculating in the groove width between roughness elements, rather than due to τ w . These results indicate the relevance of heterogeneous sorting and sizing of substrate elements to provide suitable spawning habitats in benthic environments.

Existing dataset suggests lakes in agricultural watersheds are warming faster than urban or forested lakes - Patrick T. Kelly; Kathleen Cutting; Samantha Supan; Jake Ackerman; Rebecca Erickson; Edward Pope (Aquatic Sciences, 2024)